ASSESSMENT OF THE EFFICIENCY OF USE OF EPS BY BUSINESS - Volvach, Olena (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2023)
As the world became more digitalized thanks to the Internet, it led to the creation of Electronic Payment Systems that are now used to seeing all over the world, but there is a need for estimation the return on development and implementation of EPSs. The research goal is to develop an approach based on optimization modeling for the assessment of the efficiency of implementation and the use of electronic payment systems by Ukrainian and international businesses for their day-by-day operations. The article also analyzed different classifications of EPS and determined several types of methodology for the evaluation of the effectiveness of the EPS (absolute and relative to business results and costs). Using the optimization model and system analysis, the authors proposed the algorithm for the estimation of profit from EPS implementation (both separate EPS or portfolio of EPSs) and make an experiment for one of the EPS for the period of 2023-2026. The optimization model includes revenue from EPS, as well as salary, rent, and infrastructure costs, which helps to improve the results of EPS implementation by adapting of transaction's tariff. Authors also described the process of solving optimization task for determining effective tariff per 1 transaction, taking into account marketing information.